Enhancing Firm Value Through Green Investment and Green Innovation: Does Firm Size Matter in Indonesia's Energy Industry? - Andini Ayu Lestari; Veronika Santi Paramita (Summa : Journal of Accounting and Tax, 2026)
Increased productivity in the energy sector has led to environmental degradation, requiring companies to address these challenges through green investment and green innovation as strategies to enhance corporate value. This study investigates the impact of these green initiatives on firm value and explores how company size moderates these relationships within energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2024. The research employs quantitative techniques and a descriptive-causal analysis approach. Using purposive sampling, nine out of 91 energy firms were selected. Data from financial, sustainability, and annual reports were analyzed using panel data regression and moderated regression analysis (MRA) via EViews 13. The findings indicate that green investment negatively affects firm value, whereas green innovation has a positive impact. Both factors influence firm value simultaneously. Notably, MRA results reveal that firm size strengthens the influence of green investment on firm value but does not moderate the effect of green innovation. The novelty of this research lies in demonstrating that firm size is a key factor that strengthens the influence of green investment on firm value, suggesting that the negative impact can be mitigated by larger firms' superior resource capacity. Consequently, energy companies should prioritize green innovation and enhance the efficiency of green investments. Large companies, in particular, should leverage their superior resource capacity to enhance the effectiveness of green investment in optimizing company value. Future research is encouraged to expand the sample size and observation period and to explore additional variables beyond firm size.